PENGARUH BERBAGAI KOMBINASI MEDIA LIMBAH AGROINDUSTRI TERHADAP PERTUMBUHAN DAN HASIL JAMUR MERANG (Volvariella volvaceae) - Tasyah Anjani; Slamet Abadi; Fawzy Muhammad Bayfurqon (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2022)
Straw mushroom (Volvariella volvaceae) is a type of edible mushroom life depends on where it grows. Agro-industry activities produce waste that has not been handled properly, but it is rich in lignocellulose content that can provide nutrients for edible mushrooms. The purpose of this study was to find out the best combination of agro-industrial waste media for growth and yield of edible mushroom (Volvariella volvaceae) and to determine the correlation of fruit body length, fruiting body diameter, weight per fruiting body, and number of fruiting bodies simultaneously and partially on total fruit body weight per plot. The experiment was arranged on a Completely Randomized Design (CRD), consisting of four treatments that were replicated for six times. Data were analyzed by Analysis of variance (ANOVA) at 5% level and multiple linear regression analysis. The media consisting of 50% rice straw, 25% cotton fiber, and 25% coffee husk had a significant effect and the biggest fruiting diameter of the mushroom which was 2.26 cm. The combination of f 50% rice straw + 25% cotton fiber with 25% coffee husk can gave effect on growth and yield of edible mushrooms.